(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The COVID-19 pandemic, which has been raging around the world for the past two years, has rekindled the interest of researchers in all fields in the epidemic phenomenon that has been spreading around the world since ancient times. Historians were among those interested in epidemics and their consequences in all historical periods. Given the spread of epidemics in all regions of the Old World, in particular the Christian West, the Muslim East and the Maghreb, we have chosen to study the phenomenon of major epidemics in the Maghreb in the Middle Ages from a historiographical and methodological point of view, because of the difficulties it posed for researchers due to the scarcity of sources and their eschatological nature, which constitutes a major obstacle to the approach of historical demography.